2000
DOI: 10.1152/ajpgi.2000.279.5.g961
|View full text |Cite
|
Sign up to set email alerts
|

Retention of mutant α1-antitrypsin Z in endoplasmic reticulum is associated with an autophagic response

Abstract: Although there is evidence for specific subcellular morphological alterations in response to accumulation of misfolded proteins in the endoplasmic reticulum (ER), it is not clear whether these morphological changes are stereotypical or if they depend on the specific misfolded protein retained. This issue may be particularly important for mutant secretory protein alpha(1)-antitrypsin (alpha(1)AT) Z because retention of this mutant protein in the ER can cause severe target organ injury, the chronic hepatitis/hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
267
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 266 publications
(288 citation statements)
references
References 30 publications
17
267
2
2
Order By: Relevance
“…19 Cabral et al 23 have provided evidence for a nonproteosomal degradation pathway that is sensitive to tyrosine phosphatase inhibitors. We have shown that macroautophagy contributes to disposal of retained ␣1ATZ, using chemical inhibitors 24 and cell lines genetically engineered for deficient autophagy (unpublished observations). Macroautophagy is a general stress-activated degradative mechanism whereby cytosol and intracellular organelles, such as mitochondria and parts of the ER, are first sequestered away from the rest of the cytoplasm into doublemembrane vesicles and then the vesicles fuse with the lysosome for degradation of the vesicles and their constituents (Fig.…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 89%
“…19 Cabral et al 23 have provided evidence for a nonproteosomal degradation pathway that is sensitive to tyrosine phosphatase inhibitors. We have shown that macroautophagy contributes to disposal of retained ␣1ATZ, using chemical inhibitors 24 and cell lines genetically engineered for deficient autophagy (unpublished observations). Macroautophagy is a general stress-activated degradative mechanism whereby cytosol and intracellular organelles, such as mitochondria and parts of the ER, are first sequestered away from the rest of the cytoplasm into doublemembrane vesicles and then the vesicles fuse with the lysosome for degradation of the vesicles and their constituents (Fig.…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 89%
“…16,17 Inhibition of autophagy induces aggregate formation, whereas rapamycin-induced upregulation of autophagy reduces it. [18][19][20][21] Furthermore, amelioration of neurodegeneration and improvement of behavior were reported in a D. melanogaster Huntington model following treatment with a rapamycin analog, CCI-779. 21 It has been speculated that aggregates can be degraded by autophagy Figure 2 Molecular mechanism of autophagy regulation and autophagosome formation.…”
Section: Intracellular Clearance By 'Baseline Autophagy': Antidegenermentioning
confidence: 96%
“…Autophagy selectively degrades aggregated proteins that accumulate in the ER lumen, such as the mutant secretory protein α1-antitrypsin 121 . Additionally, studies of yeast and mammalian cells demonstrate that autophagy mediates ER homeostasis by selectively segregating portions of this organelle network; this process has been termed ER-phagy or reticulophagy [122][123][124][125] .…”
Section: Box 1 | Autophagy and Protein Quality Controlmentioning
confidence: 99%